A Circular Ring Patch Antenna for Breast Cancer Detection Based on Return Loss and VSWR - Ahmed, Md. Firoz; Kabir, M. Hasnat (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2024)
Breast cancer is a serious condition that affects women and requires timely identification. Various methods such as magnetic resonance imaging, mammography, digital mammography, and computer-aided detection are used for this purpose. However, these techniques have their drawbacks. To address this issue, a new approach is proposed and detailed in this paper. In this novel method, a circular patch antenna is employed to detect tumors in a breast phantom. The analysis of return loss and voltage standing wave ratio (VSWR) helps in identifying the presence of tumors. High-frequency structure simulator (HFSS) software is employed to design and simulate the antenna for an ultra-wideband (3.1 – 10.6 GHz) frequency of 5.2 GHz, along with a breast phantom with and without a tumor. The antenna is independently simulated on both the breast phantoms with and without tumors. Rogers RT/duroid 5880 (tm) dielectric material is employed to design the antenna, with overall dimensions of 30 × 20 × 0.8 mm3. It possesses a dielectric constant of 2.2, a tangent loss of 0.02, and a thickness of 0.8 mm. The ring slot and partial ground plane techniques are employed to increase the overall effectiveness of the antenna. The properties of the antenna, such as return loss and VSWR, change when simulated with and without a tumor. The presence of a tumor within the breast is clearly indicated by the alterations in return loss and VSWR. The antenna proposed exhibits remarkable efficacy in the detection of tumors owing to its inconspicuous features, straightforward design, petite dimensions, and ideal impedance matching.